2011
DOI: 10.1016/j.ajpath.2011.02.040
|View full text |Cite
|
Sign up to set email alerts
|

Length-Dependent Retention of Carbon Nanotubes in the Pleural Space of Mice Initiates Sustained Inflammation and Progressive Fibrosis on the Parietal Pleura

Abstract: The fibrous shape of carbon nanotubes (CNTs) raises concern that they may pose an asbestos-like inhalation hazard, leading to the development of diseases, especially mesothelioma. Direct instillation of long and short CNTs into the pleural cavity, the site of mesothelioma development, produced asbestos-like length-dependent responses. The response to long CNTs and long asbestos was characterized by acute inflammation, leading to progressive fibrosis on the parietal pleura, where stomata of strictly defined siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
265
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 288 publications
(287 citation statements)
references
References 36 publications
17
265
1
4
Order By: Relevance
“…This length-dependent effect was confirmed with MWCNT-induced lesions on the inner lining of the chest wall 28 days after intrapleural exposure to MWCNTs. 26 The authors suggested that two length-dependent mechanisms are involved: (1) frustrated phagocytosis of long fibers by macrophages and (2) failure of long fibers to be cleared from the intrapleural space via stomata in the parietal pleura. 53 …”
Section: E the Effect Of Fiber Length On Cnt Potencymentioning
confidence: 99%
“…This length-dependent effect was confirmed with MWCNT-induced lesions on the inner lining of the chest wall 28 days after intrapleural exposure to MWCNTs. 26 The authors suggested that two length-dependent mechanisms are involved: (1) frustrated phagocytosis of long fibers by macrophages and (2) failure of long fibers to be cleared from the intrapleural space via stomata in the parietal pleura. 53 …”
Section: E the Effect Of Fiber Length On Cnt Potencymentioning
confidence: 99%
“…The characteristics of the different CNTs used have previously been reported in the literature by Wick et al [33] (SWCNT), Thurnherr et al [34] (MWCNT), Poland et al [24] (NTT, NTL) and Murphy et al [26] (NTS) and are detailed in Table 1. The key physico-chemical characteristics of each CNT are described in Table 1.…”
Section: Cnt Physico-chemical Characteristicsmentioning
confidence: 99%
“…Information related to the metal contaminants contained within the NTS sample was provided by the suppliers (Table 1). No endotoxin content, assessed by the limulous amoebocyte lysate (LAL) test, is known to be present within any of the CNT samples [10,24,26].…”
Section: Cnt Physico-chemical Characteristicsmentioning
confidence: 99%
“…In addition, penetration of MWCNT administrated by pharyngeal aspiration into the pleural cavity was observed, (18) and intrapleural injection of 5 lg/mouse of MWCNT has been shown to lead to sustained inflammation and length-dependent retention of MWCNT in the pleural cavity. (19) Accordingly, direct interaction of MWCNT with the mesothelial tissue is postulated as an early pathogenic event.…”
mentioning
confidence: 99%